2009
DOI: 10.1089/thy.2008.0298
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar 99mTc-Diethylenetriamine-Pentaacetic-Acid Uptake May Predict the Effectiveness of Immunosuppressive Therapy in Graves' Ophthalmopathy

Abstract: Corticosteriod treatment is associated with a decline in DTPA uptake in a fraction of GO patients. GO patients with a DTPA uptake above 12.28 MBq/cm(3) are more likely to have a favorable response to corticosteroid therapy while patients with lower values are less likely to have this potentially favorable response. An elevated DTPA uptake may identify patients who are most likely to benefit from immunosuppressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The visual image evaluation and orbital uptake fraction calculation with DTPA provide qualitative (image) and quantitative (numerical) information, respectively, on disease activity. High orbital DTPA uptake predicts the effectiveness of immunosuppressive therapy in GO [13,14]. In this twoyear long case-control study we tested if the development of GO in GD patients is predictable by DTPA SPECT.…”
Section: Discussionmentioning
confidence: 99%
“…The visual image evaluation and orbital uptake fraction calculation with DTPA provide qualitative (image) and quantitative (numerical) information, respectively, on disease activity. High orbital DTPA uptake predicts the effectiveness of immunosuppressive therapy in GO [13,14]. In this twoyear long case-control study we tested if the development of GO in GD patients is predictable by DTPA SPECT.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical usefulness of DTPA SPECT has been proven by several clinical studies from our institution [17]. Although factors of the initiation and perpetuation of the autoimmune process in GO remain unclear [18], quantitative data of orbital inflammation in GO are essential for appropriate treatment choices [19]. In disease activity measurement and prognosis estimation, the UA has been shown a useful parameter in GO by independent authors [20].…”
Section: Dtpa Uptake Values Other Diagnostic Methods and Treatment mentioning
confidence: 99%
“…This protocol was clinically tested by Galuska et al, who was able to visualize the active retrobulbar inflammation in GO patient by Tc-99m DTPA SPECT [83]. Moreover, Ujhelyi et al found that the mean retrobulbar Tc-99m DTPA uptake is useful to estimate GO activity and may predict the effectiveness of immunosuppressive therapy with corticosteroids in GO patients [84]. Especially, patients included in this study with Tc-99m DTPA uptake score above 12.28MBq/cm 3 were more likely to respond to corticosteroid treatment.…”
Section: Radionuclide-based Imaging Evaluation Of Graves' Ophthalmopathymentioning
confidence: 99%
“…Subsequently, SPECT imaging of the orbits using Tc-99mlabeled DTPA have been proposed by several reports [102][103]. This method has been accepted for evaluation of GO disease activity allowing a rapid imaging at an acceptable cost, and in addition, the successful management of GO has been associated with the decrease in orbital uptake of radiotracer [84]. In addition, to improve the sensitivity of detection of active GO phase, and therefore the prediction of the response to immunosuppressive therapy, over clinical activity score (CAS) alone, the combination of Tc-99m DTPA SPECT imaging and CAS estimation was proposed by Galuska et al [104].…”
Section: Predicting Therapeutic Efficacy and Disease Activity Based Omentioning
confidence: 99%